A new species of Deguelia (Leguminosae, Papilionoideae) from the Brazilian Amazon Basin - Camargo, Rodrigo Augusto; Tozzi, Ana Maria G. A. (Phytotaxa, 2014)
Deguelia decorticans, a new lianescent species of Leguminosae from the Brazilian Amazon, is here described and illustrated. The new species has flowers which resemble those of Deguelia duckeana and Deguelia rariflora and it might be closely related to them, probably forming a species complex. However, this new species can be easily distinguished by some morphological and reproductive characteristics.